Recent Publications (Quarterly Journal of Economics, 1964)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 78, Issue 4, November 1964, Pages 664–672, https://doi.org/10.1093/qje/78.4.664 Published: 01 November 1964